A novel 3'‐tRNAGlu‐derived fragment acts as a tumor suppressor in breast cancer by targeting nucleolin. Issue 12 (27th September 2019) - Falconi, Maurizio; Giangrossi, Mara; Zabaleta, Maria Elexpuru; Wang, Junbiao; Gambini, Valentina; Tilio, Martina; Bencardino, Daniela; Occhipinti, Sergio; Belletti, Barbara; Laudadio, Emiliano; Galeazzi, Roberta; Marchini, Cristina; et al.
Abstract : tRNA‐derived fragments (tRFs) have been defined as a novel class of small noncoding RNAs. tRFs have been reported to be deregulated in cancer, but their biologic function remains to be fully understood. We have identified a new tRF (named tRF3E), derived from mature tRNA Glu, that is specifically expressed in healthy mammary glands but not in breast cancer (BC). Consistently, tRF3E levels significantly decrease in the blood of patients with epidermal growth factor receptor 2 (HER2)‐positive BC reflecting tumor status (control > early cancer > meta‐static cancer). tRF3E down‐regulation was recapitulated in Δ16HER2 transgenic mice, representing a BC preclinical model. Pulldown assays, used to search for proteins capable to selectively bind tRF3E, have shown that this tRF specifically interacts with nucleolin (NCL), an RNA‐binding protein overexpressed in BC and able to repress the translation of p53 mRNA. The binding properties of NCL‐tRF3E complex, predicted in silico and analyzed by EMSA assays, are congruent with a competitive displacement of p53 mRNA by tRF3E, leading to an increased p53 expression and consequently to a modulation of cancer cell growth. Here, we provide evidence that tRF3E plays an important role in the pathogenesis of BC displaying tumor‐suppressor functions through a NCL‐mediated mechanism.—Falconi, M., Giangrossi, M., Elexpuru Zabaleta, M., Wang, J., Gambini, V., Tilio, M., Bencardino, D., Occhipinti, S., Belletti, B., Laudadio, E., Galeazzi, R., Marchini, C., Amici, A. A novel 39‐tRNA Glu ‐derived fragment acts as a tumor suppressor in breast cancer by targeting nucleolin. FASEB J. 33, 13228–13240 (2019). www.fasebj.org